Advanced composite armor protection systems for military vehicles: design methodology, ballistic testing, and comparison - Tsirogiannis, Evangelos Ch. (2024)
This study presents a new methodology for designing, manufacturing, and testing advanced armor protection systems and applied to the development of three different protection solutions suitable for real armored vehicles. The backplate laminates of the presented composite armor protection solutions were composed of three different materials: steel, aluminum AA6082, and aluminum alloy AA2024 reinforced by multi-walled carbon nanotubes (MWCNTs). The frontal laminates remained the same for the three cases. Keeping almost the same mass while changing the material of each backplate and adapting the thickness, the three different protection systems were ballistically tested and compared according to Level 4 (Level IV) of the standard AEP-STANAG 4569 (projectile 14.5 mm × 114 mm API B32) with real military tests. Furthermore, the performance of the total laminated structure and the performance of each backplate in the total laminated structure were compared in terms of deformation and ballistic fractures. High-quality images acquired by the high-speed camera were helpful in evaluating and comparing the backplates and the entire protection system. The results show that all three protection configurations present high performance mechanical properties and ballistic characteristics compared to commonly used armor systems. Even the under-developed AA2024-CNTs composite is a promising near-term backplate solution.